Fables Writing Skills for Class VIII Students of SMPN 2 Pakuhaji Tangerang - Emi Emi; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The research background is that the low level of students' ability to write fables is inadequate. There are some students who have adequate writing skills but are lazy to write, because the learning system is monotonous and teacher centered. The problems raised are, (1) Is there an effect of the Problem Based Learning Model on the skills of writing fables in class VIII students at SMP Negeri 2 Pakuhaji Tangerang. The method used in this study is a Quasi-Experimental type of Nonequivalent Control Group Design using experimental and control class study groups. The purpose of this study was to increase the learning activities of class VIII students of SMP Negeri 2 Pakuhaji Tangerang during the learning process using the Problem Based Learning Model, and to improve skills in writing fables through the application of the Problem Based Learning Model to class VIII students of SMP Negeri 2 Pakuhaji Tangerang. This research was conducted in two stages, namely Pretest and Posttest. The results of this study indicate that the use of the Problem Based Learning Model in fable writing skills can improve students' writing skills. The increase in students' fable writing skills can be seen from the average learning outcomes of writing skills using the Problem Based Learning Model of 70, while the average value of the results of students' fable writing skills who do not use the Problem Based Learning Model is 63. It can be concluded that the learning outcomes of students' fable writing skills experienced a significant increase.